2018
DOI: 10.1155/2018/9819402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anterior Uterocervical Angle on Primary Dysmenorrhea and Disease Severity

Abstract: Background Primary dysmenorrhea, defined as painful menstrual cramps originating in the uterus without underlying pathology, is a gynecological disease that affects quality of life and school success. Our goal was to determine the effect of anterior uterocervical angle on primary dysmenorrhea and disease severity. Methods A total of 200 virgin adolescents, 16 to 20 years of age, were included in the study. The Andersch and Milsom scale was used to determine dysmenorrhea severity. Those with pathologies causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…When the literature is reviewed, there is not much study investigating the effect of uterine length and volume on dysmenorrhea severity. However, a few studies have tried concluding the relation between uterine dimensions and pain severity by measuring only two markers including uterine or cervix length ( 9 , 10 ) , although some only measured the uterocervical angle (UCA) and others evaluated the uterus and cervix length. Unlike other studies, in the current study, we evaluated many parameters, such as uterine and cervical lengths, uterine volume, and uterine and cervix thickness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the literature is reviewed, there is not much study investigating the effect of uterine length and volume on dysmenorrhea severity. However, a few studies have tried concluding the relation between uterine dimensions and pain severity by measuring only two markers including uterine or cervix length ( 9 , 10 ) , although some only measured the uterocervical angle (UCA) and others evaluated the uterus and cervix length. Unlike other studies, in the current study, we evaluated many parameters, such as uterine and cervical lengths, uterine volume, and uterine and cervix thickness.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Sahin et al ( 9 ) has only tried to conclude dysmenorrheal severity by measuring the UCA. They showed that a narrow anterior UCA is associated with primary dysmenorrhea and disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Andersch and Milsom Scale was also used to determine the severity of dysmenorrhea according to the following grades: grade 0 (menstruation is not painful and daily activity is unaffected), grade 1 (menstruation is painful but seldom inhibits normal activity, analgesics are seldom required and mild pain), grade 2 (daily activity affected, analgesics required and give relief so that absence from work or school is unusual and moderate pain), and grade 3 (activity clearly inhibited, poor effect of analgesics, vegetative symptoms, and severe pain). Four closed questions were included on: pain intensity (not painful/mild pain/moderate pain/severe pain), working ability (unaffected/rarely affected/moderately affected/clearly affected/clearly inhibited), systemic symptoms (none/few/apparent), need for analgesia (not required/rarely required/required/poor effect) [ 18 , 30 , 31 , 32 , 33 ]. Normal menstrual characteristics were considered regular cycles of 24 to 38 days, with bleeding lasting 4.5 to 8 days, and with 5 to 80 mL blood flow [ 1 , 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, it is known that susceptibility to dysmenorrhea may be associated with genetic factors [ 11 13 ]. It is also known that the occurrence of dysmenorrhea in women is associated with an elevated secretion of prostaglandins and other inflammatory factors [ 3 , 14 , 15 ]. Prostaglandins stimulate excessive contractile function of the uterus, that leads to the reduction of blood flow and hypoxia of this organ.…”
Section: Introductionmentioning
confidence: 99%